Factors associated with kidney failure requiring hemodialysis: A case-control study - Elise Puspita Dewi; Slamet Budiyanto; Jaya Maulana; Nur Lu'lu Fitriyani (JOURNAL OF Medical Surgical Concerns, 2026)
Background: Chronic kidney disease (CKD) may progress to kidney failure requiring hemodialysis. Hypertension, diabetes mellitus, obesity, and older age are commonly associated with CKD, but local evidence remains limited. Purpose: To examine factors associated with kidney failure requiring hemodialysis among patients treated at a regional hospital in Central Java, Indonesia. Method: This case-control study included 122 participants: 61 patients receiving maintenance hemodialysis as cases and 61 controls. Cases were selected using purposive sampling and controls using consecutive sampling. Age and histories of hypertension, diabetes mellitus, and obesity were assessed using a structured questionnaire. Associations were examined using chi-square tests with continuity correction and reported as odds ratios (ORs) with 95% confidence intervals (CIs). Results: Age >60 years was not significantly associated with kidney failure requiring hemodialysis (p = 0.237; OR 0.58, 95% CI 0.26-1.26). Histories of hypertension (p = 0.016; OR 2.67, 95% CI 1.26-5.67), diabetes mellitus (p = 0.018; OR 2.84, 95% CI 1.26-6.39), and obesity (p = 0.033; OR 5.78, 95% CI 1.21-27.63) were significantly associated with the outcome. Conclusion: Hypertension, diabetes mellitus, and obesity were associated with kidney failure requiring hemodialysis, whereas age >60 years was not. These estimates are unadjusted bivariate associations and should not be interpreted as causal effects.